Religious Moderation by Design: A Comparative Sociological Da’wah Study in Indonesian Higher Education - Muliadi, Muliadi; Syamsidar, Syamsidar; Islam, Nurul (Jurnal Ilmiah Peuradeun, 2025)
This study examines the internalization of religious moderation values among students at Islamic Higher Education Institutions (PTKI) and Public Higher Education Institutions (PTU) in South and West Sulawesi, Indonesia. Amid concerns over rising religious intolerance and extremism, higher education is increasingly seen as a strategic arena for fostering inclusive values. PTKI, by design, promotes moderate Islamic teachings, but comparative evidence between PTKI and PTU remains underexplored. Adopting a quantitative comparative approach, the study surveyed 400 students to measure their perceptions across four dimensions: national commitment, tolerance, anti-violence, and accommodation of local culture. Results show that PTKI students consistently score higher than their PTU counterparts across all dimensions. For example, PTKI students recorded a higher mean score in anti-violence (2.88) compared to PTU (2.53), and similar gaps are found in other areas. These findings demonstrate the effectiveness of PTKI in shaping moderate and pluralistic religious identities through structured curricula and institutional culture. The study contributes to educational and socio-religious discourse by highlighting how religious education, when aligned with national values, can counter radicalism and promote social harmony. This study offers a novel comparative framework that integrates sociological da’wah and self-perception theory to empirically assess how institutional environments shape students’ internalization of religious moderation in higher education.